HUBUNGAN KECEPATAN DAN KELINCAHAN TERHADAP KEMAMPUAN MENGGIRING BOLA PEMAIN SSB BINA MITRA KECAMATAN SUNGAI APIT - Jumaldi Rizki; Saripin Saripin; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is SSB football players Bina Mitra Sungai Apit Subdistrict not optimal in dribble well when playing football. This is allegedly the lack of speed and agility owned by player of SSB  Bina Mitra when dribbling so easy to read and easily taken by opponents. The purpose of this study is to determine whether there is a relationship of speed and agility to the ability to accompany ball players SSB Bina Mitra Sungai Apit District. In this research is SSB Bina Mitra Kecamatan Sungai Apit which amounted to 20 people. The sample in this study is less than one hundred then the samples taken by (total sampling) or sampling technique in full of SSB players Bina Mitra District River Apit which amounted to 20 people. The design of this study is a correlational study by comparing the measurement results of two different variables in order to determine the level of relationship between variables. As the free variable speed ( ) and agility ( ) while the dependent variable (Y) is dribbling / dribbling. this test uses the type of correlation research, then the test data using the test of normality test, product test moment correlation, variable normality test Lomax (0,128) < Ltabel (0,190), variable normality test  Lomax (0,148) < Ltabel (0,190), and test normality variable Y Lomax (0,084) < Ltabel (0,190). In other words ,  and Y data levels are normally distributed. Keywords: Football, Speed of Dribbling, Agility Lead.